2012
DOI: 10.1179/1743280411y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Modern HSLA steels and role of non-recrystallisation temperature

Abstract: The use of heavy gauge steel sheets for structural applications often requires a combination of high yield strength and adequate toughness. The most cost effective way to achieve high yield strength and high ductility in low alloyed steels is through grain refinement. In industrial practice, such refinement is commonly obtained by thermomechanical controlled processing (TMCP). This approach comprises slab reheating to well defined temperatures, a large amount of hot deformation below the non-recrystallisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 106 publications
3
162
0
7
Order By: Relevance
“…The shape of the recrystallised fraction versus time curves were similar for the microalloyed steels used, it being observed that some curves display a plateau caused by the formation of precipitates which momentarily inhibit the progress of recrystallisation [34][35][36][37]. The plateau is caused by strain-induced precipitation, as occurs in all microalloyed steels, and the start and end of the plateau are identified approximately with the start and end of strain-induced precipitation, respectively.…”
Section: Precipitation Start-time-temperature (Pstt) Diagrams For Twomentioning
confidence: 72%
See 1 more Smart Citation
“…The shape of the recrystallised fraction versus time curves were similar for the microalloyed steels used, it being observed that some curves display a plateau caused by the formation of precipitates which momentarily inhibit the progress of recrystallisation [34][35][36][37]. The plateau is caused by strain-induced precipitation, as occurs in all microalloyed steels, and the start and end of the plateau are identified approximately with the start and end of strain-induced precipitation, respectively.…”
Section: Precipitation Start-time-temperature (Pstt) Diagrams For Twomentioning
confidence: 72%
“…After the plateau, the superiority of driving forces for recrystallisation over pinning forces is about two orders of magnitude [6]. In Nb-microalloyed steels the Nb atoms/NbCN precipitates retard the recrystallisation of deformed austenite [7][8][9][10]. However, V-microalloyed steels also exhibit grain refinement through intragranular nucleation of ferrite on VN precipitates partly due to low lattice mismatch of VN with ferrite [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This may involve both dynamic and static recrystallization and also strain induced precipitation of carbonitrides of niobium and vanadium and possibly titanium carbide, all which influence the mechanical and toughness properties. When they are fine (10-25nm), these precipitates provide dispersion hardening and when they are larger (20-50nm), depending on their volume fraction, grain refinement through grain boundary pinning [15][16][17]. Some or all of these processes might be expected may take place during the FSW of microalloyed steel, as has been discussed in a recent report [18].…”
Section: Introductionmentioning
confidence: 92%
“…Independently of the employed processing, grain refinement and strain accumulation are the keys for achievement good properties of the rolled and forged materials [7]. It is well known that the reduction of grain size will introduce homogeneity in the deformation [8,9] and, in addition, the grain refinement increases the strength of an alloy, according to the Hall-Petch's relationship, leading to a better mechanical behavior after processing. In fact, reduction of grain size is the unique mechanism that increases both strength and toughness [10,11].…”
Section: Introductionmentioning
confidence: 99%